Institutional repository activities in Kenneth Dike Library, University of Ibadan, Nigeria (2022)
There is a glaring divide between institutional literature and the user community. Institutional Repository (IR) deals with bridging the gap between institutions’ ever growing educational and research output, and the users of the materials for teaching/learning, research, decision making and societal advancement. According to literature, the pace of adoption of IR has been slow and quit uneven especially in the developing world with very few universities adopting IR in Nigeria. In the light of the innumerable benefits of institutional repository, Kenneth Dike Library has joined university libraries all over the world in the adoption of institutional repository. The paper examined the institutional repository of Kenneth Dike Library, University of Ibadan (UI) which is a Premier university in Nigeria. The study adopted survey method. Interview instrument was used for the study. The basic information about UI institutional repository development and management procedures were obtained through a face-to-face interview with some of the library’s systems staff that are knowledgeable on the university’s IR. The study identified the procedural activities in the IR development at Kenneth Dike Library (KDL), which include strategic planning of the project by UI library management, seeking for and obtaining the university management’s approval, the adoption of in-house approach to digitization and management of IRs, and the continual digitization processes. Finally the study indicated some problems and solutions in the management of University of Ibadan IR project which could be of help to those institutions that are yet to establish IRs.